A study on motivational factors that influence employee performance at Majlis Perbandaran Sungai Petani Kedah (MPSPK) / Nurulhanim Aqela Zakaria and Siti Humairah Abdul Hamid - Zakaria, Nurulhanim Aqela Zakaria; Abdul Hamid, Siti Humairah (2018)
Employee perfonnance is an important principle for the successfulness of local governments. It is important as local governments cover up 70% of the population and an important institution in Malaysia. The extent of employee perfonnance in local government will indicates the perfonnance of the employees. In addition, motivation is one of the factors that can enhance the employee perfonnance in local governments. Therefore, this study aims to examine the relationship between motivational factors which include recognition, working environment, training and communication. A survey was conducted at Majlis Perbandaran Sungai Petani Kedah (MPSPK). TI1e data were collected using a self-administrated questionnaire from 165 respondents using a systematic sampling technique. However, only 148 responses with 89.7% response rate were deemed suitable for further analysis. The result of this study indicates that there is high extent of employee perfonnance at MPSPK and communication is the most dominant factor that influences employee perfonnance at MPSPK. This study also shows that all hypothesis on motivational factors listed were accepted.